A knowledge synthesis of culturally- and spiritually-sensitive end-of-life care: findings from a scoping review. Issue 1 (December 2016) - Fang, Mei; Sixsmith, Judith; Sinclair, Shane; Horst, Glen
Abstract Background Multiple factors influence the end-of-life (EoL) care and experience of poor quality services by culturally- and spiritually-diverse groups. Access to EoL services e.g. health and social supports at home or in hospices is difficult for ethnic minorities compared to white European groups. A tool is required to empower patients and families to access culturally-safe care. This review was undertaken by the Canadian Virtual Hospice as a foundation for this tool. Methods To explore attitudes, behaviours and patterns to utilization of EoL care by culturally and spiritually diverse groups and identify gaps in EoL care practice and delivery methods, a scoping review and thematic analysis of article content was conducted. Fourteen electronic databases and websites were searched between June–August 2014 to identify English-language peer-reviewed publications and grey literature (including reports and other online resources) published between 2004–2014. Results The search identified barriers and enablers at the systems, community and personal/family levels. Primary barriers include: cultural differences between healthcare providers; persons approaching EoL and family members; under-utilization of culturally-sensitive models designed to improve EoL care; language barriers; lack of awareness of cultural and religious diversity issues; exclusion of families in the decision-making process; personal racial and religious discrimination; and lack of culturally-tailored EoL information to facilitate decision-making. Conclusions This review highlights that most research has focused on decision-making. There were fewer studies exploring different cultural and spiritual experiences at the EoL and interventions to improve EoL care. Interventions evaluated were largely educational in nature rather than service oriented.